Craniofacial Tissue Simulation Using Contact Analysis Of The Finite Element Method - Obaidellah, Unaizah; Azizul, Zati; Mohd Faizal, Erma Rahayu (Malaysian Journal of Computer Science, 2014)
A corrective surgery known as the craniofacial surgery is important for the improvement of a patient’s appearance and in some cases a patient’s physical abilities in terms of speech. The postoperative soft tissues prediction is often a hit considering the complex facial anatomy. Such surgical planning may be made simpler and more precise with the use of computational modelling of the relevant area. This paper presents a general framework for the simulation of soft tissue in order to predict the postoperative results of maxillofacial surgery based on the finite element method. Methods for the facial model preparation used in the analysis are described. A 3D facial model of the facial skin and the underlying lower jaw is modelled from a patient-specific CT data. In conjunction with the representation of soft tissue mechanical properties and boundary assignment, the models were submitted for a contact analysis for a computational postoperative appearance. Finally the simulation results are shown for the case study data.